The Effect Of Roa, Leverage, Sales Growth, And Firm Size On Tax Avoidance In Healthcare Entities On The Indonesian Stock Exchange From 2014 To 2023 - Surya, Christine Tania (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research was conducted to examine the effect of return on asset, leverage, firm size, and sales growth on tax avoidance in healthcare entities listed on the Indonesia Stock Exchange (IDX) from 2014 to 2023. The data used in this study are secondary data obtained from the Indonesia Stock Exchange website or the official website of each healthcare entity. The sample used in this research consists of healthcare entities selected through purposive sampling. The analysis employed in this study is panel data regression analysis to test the effect of the independent variables on the dependent variable. The results of this study show that return on asset affect tax avoidance, leverage does not affect tax avoidance, firm size affect tax avoidance, and sales growth does not affect tax avoidance.